Pressure relief and control technology for gob-side roadway in soft and thick coal seam in kilometer-deep coal mine - Wenwei MA; Wenxu LIANG (Meikuang Anquan)
In order to solve the control problems of deformation and failure in soft and thick coal seam in kilometer-deep coal mine, the gob-side roadway in deep loose and weak thick coal seam is taken as the object. Based on on-site investigation and measurement, the obtained the mechanical strength and structural distribution of coal roadway surrounding rock reveal the deformation and failure characteristics of surrounding rock of high stress coal roadway in deep mine; through a constructed three-dimensional numerical model for surrounding rock of a kilometer deep soft coal roadway, and the the effect of pressure relief hole length and spacing on the pressure relief control of coal roadway were analyzed. A reasonable spacing of 1.0 m and a depth of 10.0 m for pressure relief holes are obtained. Key control technical parameters such as strong support for surrounding rock of gob-side roadway and drilling pressure relief are proposed. The rationality of pressure relief control technology and parameters is verified through combined observation methods such as surrounding rock displacement and anchor cable stress.